Kompetensi Guru Dalam Perspektif Pendidikan Islam - Edy, Edy; Maryam, Siti (Edusifa: Jurnal Pendidikan Islam, 2022)
In the world of education the meaning of "competence" is then translated as a set of knowledge, skills and behaviors that must be possessed, internalized and controlled by a teacher or lecturer in carrying out professional duties. Competence can also be interpreted as knowledge, skills and basic values ​​that are reflected in the habits of thinking and acting. Thus, the competencies possessed by each teacher will show the true quality of teachers. In law number 14 of 2005 concerning teachers and lecturers it is stated that teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing and evaluating. students in early childhood education, formal education, primary and secondary education. Teachers as professional educators must have abilities that are not possessed by other professional positions related to what competencies are possessed by teachers. A teacher is required to have academic qualifications, competencies, and educator certificates as formal evidence that the educator has the expected skills. In Islamic education the term teacher is referred to as Ustadz, Mu'allim, Murabbî, Mursyîd, Mudarris, Muaddib where for a long time the scholars have determined teacher competencies which include physical requirements (good body shape; sweet face/beautiful; wide forehead; and his forehead was open from his hair. -clean-faced-).and . Psychic requirements (sound sense, civilized heart, sharp understanding, fair, officer in nature, broad chest, when speaking first imagine in his heart, can choose noble and good words, clear words, easy to understand and relate to each other, stay away from everything which leads to ambiguous speech). keywords: Competence, Teachers, Islamic Religious Education